Supporting Livelihoods with New Varieties of Cassava for the Yali Reservoir - CGIAR Challenge Program on Water and Food (2014)
This CPWF Outcome Story details efforts to improve livelihoods for dam-affected communities in Viet Nam through the introduction of a new variety of short-duration cassava.